The Effect of Natural Health Products and Traditional Medicines on the Activity of Human Hepatic Microsomal-Mediated Metabolism of Oseltamivir - Rui Liu; Teresa W Tam; Jingqin Mao; Ammar Saleem; Anthony Krantis; John T Arnason; Brian C Foster (Frontiers Media S.A., 2010)
Purpose. Oseltamivir is a prodrug that requires metabolic activation but there is little information on whether natural health products interact to prevent the biotransformation by the carboxylesterase. Methods. HPLC-DAD-ESI-MSD and fluorometric assays were used to determine if 50-pooled mixed gender human liver microsomes can mediate the formation of the active carboxylate metabolite and then if this reaction is affected by natural health products. Results. Extracts from 6 traditional Cree botanicals, a commercially available Echinacea product, Goldenseal and a traditional Chinese medicine reduced the formation of the active drug. In addition to oseltamivir carboxylate we report the detection of two new metabolites which are derivatives of oseltamivir carboxylate, one of which is a metabonate formed as a result of methanol. Conclusions. In vitro studies would suggest that there is the potential for some natural health products used by patients in response to pandemic A/H1N1 to reduce drug efficacy. Further studies are required to determine if these potential interactions could be clinically significant.